Real‐time PCR based HLA‐B*27 screening directly in whole blood. (1st December 2019) - Geiger, Kathrin; Zach, Christina; Leiherer, Andreas; Fraunberger, Peter; Drexel, Heinz; Muendlein, Axel
Abstract : The linkage between the occurrence of human leucocyte antigen B*27 ( HLA‐B*27 ) and ankylosing spondylitis or other related spondyloarthritides is well documented. PCR based methods are widely used for HLA‐B*27 screening. To refine HLA‐B*27 testing we aimed at establishing a real‐time PCR protocol to detect the HLA‐B*27 allele directly in blood samples, without DNA extraction. HLA‐B*27 analysis was performed by two real‐time PCRs using TaqMan primer‐probe assays for B*27 specific amplification of exon 2 or exon 3 of the HLA‐B gene together with a mutant of Taq polymerase for direct blood PCR. Conditions for direct blood PCR were optimized and the reliability of the direct blood PCR protocol was evaluated by re‐genotyping over 200 blood samples from patients who previously underwent routine DNA‐based HLA‐B*27 testing. Heating blood samples at 95°C for 10 minutes significantly improved PCR performance. Results from real‐time PCR based HLA‐B*27 testing directly in blood of over 200 patients were in 100% concordance with results obtained by routine DNA‐based HLA‐B*27 genotyping. In summary, we present a reliable real‐time PCR protocol for HLA‐B*27 screening directly in whole blood supporting fast clarification of the presence of ankylosing spondylitis or other spondyloarthritides in suspected cases.